Clinical Use of Schistosoma mansoni Antigens as Novel Immunotherapies for Autoimmune Disorders - Cleenewerk, L.; Garssen, Johan; Hogenkamp, Astrid (Frontiers in Immunology, 2020)
The hygiene hypothesis states that improved hygiene and the resulting disappearance of once endemic diseases is at the origin of the enormous increase in immune related disorders such as autoimmune diseases seen in the industrialized world. Helminths, such as Schistosoma mansoni, are thought to provide protection against the development of autoimmune diseases by regulating the host’s immune response. This modulation primarily involves induction of regulatory immune responses, such as generation of tolerogenic dendritic cells and alternatively activated macrophages. This points towards the potential of employing helminths or their products/metabolites as therapeutics for autoimmune diseases that are characterized by an excessive inflammatory state, such as multiple sclerosis (MS), type I diabetes (T1D) and inflammatory bowel disease (IBD). In this review, we examine the known mechanisms of immune modulation by S. mansoni, explore preclinical and clinical studies that investigated the use of an array helminthic products in these diseases, and propose that helminthic therapy opens opportunities in the treatment of chronic inflammatory disorders.